Extracellular Granzyme K Modulates Angiogenesis by Regulating Soluble VEGFR1 Release From Endothelial Cells - Li, Shuang; van Dijk, Christian G. M.; Meeldijk, Jan; Kok, Helena M.; Blommestein, Isabelle; Verbakel, Annick L. F.; Kotte, Marit; Broekhuizen, Roel; Laclé, Miangela M.; Goldschmeding, Roel; Cheng, Caroline; Bovenschen, Niels (Frontiers in Oncology, 2021)
Angiogenesis is crucial for normal development and homeostasis, but also plays a role in many diseases including cardiovascular diseases, autoimmune diseases, and cancer. Granzymes are serine proteases stored in the granules of cytotoxic cells, and have predominantly been studied for their pro-apoptotic role upon delivery in target cells. A growing body of evidence is emerging that granzymes also display extracellular functions, which largely remain unknown. In the present study, we show that extracellular granzyme K (GrK) inhibits angiogenesis and triggers endothelial cells to release soluble VEGFR1 (sVEGFR1), a decoy receptor that inhibits angiogenesis by sequestering VEGF-A. GrK does not cleave off membrane-bound VEGFR1 from the cell surface, does not release potential sVEGFR1 storage pools from endothelial cells, and does not trigger sVEGFR1 release via protease activating receptor-1 (PAR-1) activation. GrK induces de novo sVEGFR1 mRNA and protein expression and subsequent release of sVEGFR1 from endothelial cells. GrK protein is detectable in human colorectal tumor tissue and its levels positively correlate with sVEGFR1 protein levels and negatively correlate with T4 intratumoral angiogenesis and tumor size. In conclusion, extracellular GrK can inhibit angiogenesis via secretion of sVEGFR1 from endothelial cells, thereby sequestering VEGF-A and impairing VEGFR signaling. Our observation that GrK positively correlates with sVEGFR1 and negatively correlates with angiogenesis in colorectal cancer, suggest that the GrK-sVEGFR1-angiogenesis axis may be a valid target for development of novel anti-angiogenic therapies in cancer.